Development of grease resistant to water washout - S. V. Pashukevich (Омский научный вестник)
In the work, laboratory tests are carried out to create a grease with the introduction of waterproof components into the composition with further analysis of samples of the resulting lubricant. A technique has also been developed to measure the washout of greases. During the tests, the values of the following technological properties of greases are obtained: dropping point, penetration at 25 °C with stirring, colloidal stability, welding load, washout, freezing point, tensile strength at 20 °C and at 80 °C. A comparative analysis of each of the considered indicators of five samples of the developed lubricant and samples of already manufactured products are carried out.